1974
DOI: 10.1128/iai.9.4.669-673.1974
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Production by Macrophages from Adult and Newborn Rabbits Bearing Fibroma Virus-Induced Tumors

Abstract: Tumors were induced in adult and newborn rabbits by inoculation of fibroma virus. After 10 to 14 days, oil-induced peritoneal macrophages were harvested, purified, and tested in vitro for interferon synthesis after stimulation with specific and nonspecific viruses. Peritoneal macrophages from adult rabbits that had initiated tumor regression produced high levels of interferon (titers ranged from 160 to 640) after stimulation with fibroma virus, whereas macrophages from normal adult rabbits failed to produce si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1974
1974
1991
1991

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Although cultures of immune macrophages contain no infectious fowlpox virus, the possibility of virus antigens cannot be excluded since macrophages were recovered from chickens with active fowlpox lesions known to contain virus antigen (11). However, studies by Pathak and Tompkins (16) suggest that nonspecific immunity to fibroma virus in rabbits is not due to virus antigens in the cultures. Unstimulated macrophage cultures from normal and fibroma-immune rabbits failed to produce significant levels of interferon in vitro and only immune macrophage cultures responded to subsequent challenge.…”
Section: Discussionmentioning
confidence: 98%
“…Although cultures of immune macrophages contain no infectious fowlpox virus, the possibility of virus antigens cannot be excluded since macrophages were recovered from chickens with active fowlpox lesions known to contain virus antigen (11). However, studies by Pathak and Tompkins (16) suggest that nonspecific immunity to fibroma virus in rabbits is not due to virus antigens in the cultures. Unstimulated macrophage cultures from normal and fibroma-immune rabbits failed to produce significant levels of interferon in vitro and only immune macrophage cultures responded to subsequent challenge.…”
Section: Discussionmentioning
confidence: 98%
“…Experiments from other laboratories also have shown that leukocytes from animals immune to a specific antigen (viral or nonviral) produced more interferon when exposed to that antigen than leukocytes from nonimmune animals (11)(12)(13)(14)(15)(16)(17)(18)(19). Recently, Youngner and Salvin (17) reported that immunologically induced interferon differs in its physical properties from nonimmunologically induced interferon; at pH 2.0 the interferon was inactivated.…”
Section: Discussionmentioning
confidence: 99%
“…This might be one of the explanations for the lower amount of interferon produced in our experiments by splenic as compared to peritoneal leukocytes. The specific cell type(s) producing interferon in our system also remains to be determined, but evidence from other laboratories indicates that both immune lymphocytes and macrophages can produce interferon (12,15,18).…”
Section: Discussionmentioning
confidence: 99%
“…control animals, a process thought to be mediated by inter- have been examined directly for the production of interferon in the host, and increases in the levels of interferon can be detected in serum, peritoneal exudate cells, spleen, liver, and lymph node and in extracts of lesions (174,191,362,390,436,466,496). The recovery of interferon from the site of vaccinia virus inoculations of guinea pigs prompted Friedman et al (174) to suggest that interferon was the protective element in guinea pigs that were immunocompromised by treatment with methotrexate and X rays (no detectable neutralizing antibody or DTH reaction).…”
Section: Interferonsmentioning
confidence: 99%
“…Human peripheral blood lymphocytes (PBL) from immune individuals make gamma interferon following stimulation in vitro with viral antigen(141). Additionally, perito-2 y ., neal exudate cells isolated from adult rabbits with tumors 0 q , D , induced by SFV (Patuxent strain) produced more interferon upon challenge with virus than did cells obtained from either g0 t E vnonimmune or neonatal rabbits(362).In vivo influence of interferon and interferon inducers on = Q 8 poxvirus pathogenesis. The effects of interferon on poxvirus r 5areplication in vivo have been examined by correlating inter-= z eX feron levels with the severity of disease or by measuring = nr QQ disease parameters in animals treated with interferon, inter-o°Z <^> t 3 > feron inducers, and immunomodulators.…”
mentioning
confidence: 97%